A New Thermophilic Nitrilase from an Antarctic Hyperthermophilic Microorganism - Dennett, Geraldine V.; Blamey, Jenny M. (Frontiers in Bioengineering and Biotechnology, 2016)
Several environmental samples from Antarctica were collected and enriched to search for microorganisms with nitrilase activity. A new thermostable nitrilase from a novel hyperthermophilic archaea Pyrococcus sp. M24D13 was purified and characterized. The activity of this enzyme increased as the temperatures rise from 70 up to 85 °C. Its optimal activity occurred at 85 °C and pH 7.5. This new enzyme shows a remarkable resistance to thermal inactivation retaining more than 50% of its activity even after 8 h of incubation at 85 °C. In addition, this nitrilase is highly versatile demonstrating activity towards different substrates such as benzonitrile (60 mM, aromatic nitrile) and butyronitrile (60 mM, aliphatic nitrile), with a specific activity of 3286.7 U mg-1 of protein and 4008.2 U mg-1 of protein respectively. Moreover the enzyme NitM24D13 also presents cyanidase activity. The apparent Michaelis-Menten constant (Km) and Vmáx of this Nitrilase for benzonitrile were 0.3 mM and 333.3 µM min-1, respectively, and the specificity constant (kcat/Km) for benzonitrile was 2.05×105 s-1 M-1.